DESKRIPSI KARATERISTIK LUKISAN SISWA SMP NEGERI 1 PADANG - Jeni Gunawan, Dr. Ramalis Hakim, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
The purposes of this research are: (1) to describe the paintings among ninthgrade junior high school students of SMP Negeri 1 Padang based on childrenpaintings periodisation, (2) to know the characteristics of ninth grade junior highschool students' paintings of SMP Negeri 1 Padang based on the children paintings typology. The type of this research is descriptive qualitative research. Collecting data technic is through literatures study, observation, interview, and documentation. Data analysis uses flow model of analysis (flowing model) which includes data reduction, data providing, and conclusion determination, while for explaining the periodisation and types of painting art uses analysis interpretation based on children paintings periodisation and typology theories by Lowenfeld. Result of this research shows that 15 students' paintings show characteristics unmatched with children paintings periodisation theory of Lowenfeld. Then the characteristics of 15 other paintings match to the children paintings development periodisation of Viktor Lowenfeld. Result of this research shows that 15 students' paintings show characteristics unmatched with children paintings periodisation theory of Lowenfeld. And the characteristics based on the paintings typology, general paintings type which is appeared in the paintings among ninth grade junior high school students of SMP Negeri 1 Padang is visual type, in total of 23 paintings.Keywords: Paintings, Characteristics, Students, Junior High School